Acceptability of programme budgeting and marginal analysis as a tool for routine priority setting in Indigenous health. (11th March 2015) - Otim, Michael E.; Asante, Augustine D.; Kelaher, Margaret; Anderson, Ian P.; Jan, Stephen
Abstract: Objective: This study aimed to examine the acceptability of programme budgeting and marginal analysis (PBMA) as a tool for priority setting in the Indigenous health sector. Methods: The study uses a mix of quantitative and qualitative methods. A survey of key decision makers in Indigenous health in Victoria was conducted to assess the acceptability of PBMA as a potential tool for priority setting. Respondents comprised 24 bureaucrats from the Victorian Department of Human Services (DHS) and 26 senior executives from the aboriginal community controlled health sector (ACCHS) in Victoria. The survey instrument included both closed‐ended and open‐ended questions and was administered face‐to‐face by a trained researcher in 2007–2008. Closed‐ended questions were analysed using descriptive statistics, and content analysis was used for the open‐ended ones. Results: The PBMA was well received as having the potential to improve priority setting processes in Indigenous health. Sixty‐nine percent of the DHS respondents felt that PBMA was acceptable as a routine decision‐making tool, and nearly 80% of ACCHS respondents thought that PBMA was intuitively appealing and would most probably be an acceptable priority setting approach in their organisations. The challenges of using PBMA were related to resource constraints and data intensity. Conclusion: Programme budgeting and marginal analysis is potentially acceptable within the ACCHS and was perceived as useful in terms of assisting the decision maker to maximise health outcomes, but data systems need to be re‐oriented to address its significant data needs. Implication: Proper guidelines need to be developed to facilitate PBMA application within the Indigenous‐controlled community health sector. Copyright © 2015 John Wiley & Sons, Ltd.